Experiencia de trabajo docente: análisis de caso en la unidad educativa Pedro Maldonado del cantón Otavalo - Inlago Bautista, Wilmer Vinicio (2016)
This research is made based on the experiences of decent work, which will enable readers to find content that would help correct mistakes we make now at the time of the pedagogical application, i.e. that the narrative of school practices documentation is a mode of inquiry and educational action aimed to rebuild, make publications and interpret the senses and meanings that teachers produce and put into play when they write read, reflect, and talk among colleagues about her own educational experiences, contribute aspects of organizational character as one of the strengths that exceeds all limits on existing conflicts already within a teaching exercise, research also includes the process of systematizing the experiences that this Professor lives would constitute a form of reasoning what can serve us in the apprehension and conceptualization of our specific experiences.